1999
DOI: 10.1348/000709999157699
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal perspective on learning strategies in higher education ‐ different view‐points towards development

Abstract: Background. An important purpose of tertiary education is that students develop more advanced, deep-level learning. Longitudinal, within-subject studies to examine intra-individual changes, however, are scarce. Aims.We aimed at gaining a broad picture of students' development in academic learning by taking many different perspectives. This involves the extent to which students report change, factors that contribute to this, the degree of stability of different aspects of learning, and changes in their interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
2
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 24 publications
10
86
2
9
Order By: Relevance
“…Mediating influences might include a greater motivation for undertaking the additional qualification, the increased costs associated with the second degree (postgraduate students are required to pay approximately fivefold greater fees), and the older students' more mature outlook towards study.-The results of this study are more encouraging than those of the cross-sectional study in terms of observing development of students' approaches to learning over time. In common with the study by Vermunt and colleagues, 17,18 students in both the BPharm and MPharm cohorts in this study demonstrated significant increases over the course of their study in their preference for deep-processing strategies and self-regulation. In both cohorts, differences in curriculum and delivery may have been mediating factors in some of the observed changes; however, further research is necessary to elucidate the mechanisms by which any mediation occurred.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mediating influences might include a greater motivation for undertaking the additional qualification, the increased costs associated with the second degree (postgraduate students are required to pay approximately fivefold greater fees), and the older students' more mature outlook towards study.-The results of this study are more encouraging than those of the cross-sectional study in terms of observing development of students' approaches to learning over time. In common with the study by Vermunt and colleagues, 17,18 students in both the BPharm and MPharm cohorts in this study demonstrated significant increases over the course of their study in their preference for deep-processing strategies and self-regulation. In both cohorts, differences in curriculum and delivery may have been mediating factors in some of the observed changes; however, further research is necessary to elucidate the mechanisms by which any mediation occurred.…”
Section: Discussionsupporting
confidence: 82%
“…While 2 studies of university students' progression through their degree programs found increases in deep-processing strategies and self-regulated learning behaviors, another investigation of university students showed no improvements in productive approaches over time. [17][18][19] Hastings et al's study of pharmacy students' motivation over the course of their degree revealed significant decreases in their desire to develop mastery and deep understanding of course material. 20 Similarly, Sansgiry found that the quality of pharmacy students' study strategies decreased over the 3 years of the degree program.…”
Section: Approaches To Learningmentioning
confidence: 99%
“…Desde esta línea de investigación se establecen básicamente dos enfoques de aprendizaje: el superficial y el profundo (Entwistle y Ramsden, 1983). El enfoque profundo se relaciona con: el uso de estrategias profundas para el aprendizaje constructivista (Biggs, 1987;Hernández Pina y Hervás, 2005), la aplicación de estrategias metacognitivas (Vermetten, Vermunt y Lodewijks, 1999;Martínez-Fernández, Villegas y Martínez Torres, 2004) y una tendencia hacia las funciones legislativas y judicial de los estilos de pensamiento, pero no hacia la función ejecutiva (Zhang, 2000;Zhang y Sternberg, 2000;Rosário et al, 2005).…”
Section: Los Estilos De Pensamiento Y Las Estrategias Metacognitivasunclassified
“…A similar pattern of results was found in a first-and second-year sample of 276 students from law, economics, social sciences, and languages disciplines. 17 However, conflicting results were found by Busato et al 18 among a group of 477 first-to fifth-year psychology students. Students did not score higher on productive approaches to learning and did not have increased vocational orientation as they progressed through the curriculum.…”
Section: Introductionmentioning
confidence: 96%